Tenascin-C and mechanotransduction in the development and diseases of cardiovascular system - Imanaka-Yoshida, Kyoko; Aoki, Hiroki (Frontiers in Physiology, 2014)
Living tissue is composed of cells and extracellular matrix (ECM). In the heart and blood vessels, which are constantly subjected to mechanical stress, ECM molecules form well-developed fibrous frameworks to maintain tissue structure. ECM is also important for biological signaling, which influences various cellular functions in embryonic development, and physiological/pathological responses to extrinsic stimuli. Among ECM molecules, increased attention has been focused on matricellular proteins. Matricellular proteins are a growing group of non-structural ECM proteins highly up-regulated at active tissue remodeling, serving as biological mediators. Tenascin-C (TNC) is a typical matricellular protein, which is highly expressed during embryonic development, wound healing, inflammation, and cancer invasion. The expression is tightly regulated, dependent on the microenvironment, including various growth factors, cytokines and mechanical stress. In the heart, TNC appears in a spatiotemporal-restricted manner during early stages of development, sparsely detected in normal adults, but transiently re-expressed at restricted sites associated with tissue injury and inflammation. Similarly, in the vascular system, TNC is strongly up-regulated during embryonic development and under pathological conditions with an increase in hemodynamic stress. Despite its intriguing expression pattern, cardiovascular system develops normally in TNC knockout mice. However, deletion of TNC causes acute aortic dissection under strong mechanical and humoral stress. Accumulating reports suggest that TNC may modulate the inflammatory response and contribute to elasticity of the tissue, so that it may protect cardiovascular tissue from destructive stress responses. TNC may be a key molecule to control cellular activity during development, adaptation or pathological tissue remodeling.